Curative effect of stereotactic body radiotherapy for unresectable massive primary liver cancer - Dang, Ya-Zheng (Mol Clin Oncol, 2017)
The aim of this study was to evaluate the curative effect of gamma knife stereotactic body radiotherapy (SBRT) for unresectable massive primary liver cancer. A total of 69 patients with unresectable massive (>10 cm) primary liver cancer who were treated by SBRT at the Department of Radiation Oncology of the 323 Hospital of People's Liberation Army (Xi'an, China) between October, 2006 and October, 2010, were analyzed. According to the Union for International Cancer Control TNM staging guidelines, the patients were graded as stage T1 (n=8), T2 (n=12), T3 (n=21) and T4 (n=28). None of the patients had lymph node metastasis, whereas 45 patients had portal vein tumor thrombosis. The Child-Pugh class was A (n=49), B (n=15) and C (n=5). The visible tumor volume ± standard deviation was 810±213 cm(3). The patients received a total radiation dose of 50–60 Gy, with a dose fractionation of 4–6 Gy/fx, administered for a total of 9–12 times, 2–5 times/week. A total of 8 patients succumbed to the disease within 3 months after gamma knife treatment and were not included in the evaluation of the curative effect. The total effectiveness rate was 59.0% (36/61) and the median survival was 17.4 months for all the patients included in the study. The 1-, 2-, and 3-year overall survival rates were 71, 30 and 22%, respectively. In conclusion, SBRT appears to be effective for unresectable massive primary liver cancer.